Damage severity evaluation methods for biocomposite vertical axis wind turbine blades due to lightning strikes - Mat Daud, Siti Zubaidah (2018)
In the wind turbine industry, damage occurs in many parts of the wind turbine, such as the tower, the gearbox, the shaft and the rotor blade etc., but the most common damage occurs in the rotor blade and the tower. More attention required on the structural health of the rotor blades since they play a significant role in the wind turbine system, accounting for 15-20% of the entire turbine cost and resulting in an expensive repair cost when damage occurs. The most common causes of rotor blade damage are wind gusts, heavy rainfall and lightning strikes. Over 30% is affected by thunderstorms or lightning strikes, 28.21% by heavy rainfall and 15.3% by strong winds. Wind turbines are susceptible to lightning strikes since their size is becoming larger and it is predictable that they will be more exposed to lightning strikes in the future. Therefore, this thesis focused on lightning strike behaviour with respect to rotor blades for both composite and biocomposite material. The literature review highlighted wind energy, lightning damage on rotor blades and the types of damage detection used. The main objective of this thesis is to determine the lightning strike behaviour with respect to biocomposite, hybrid and composite material. The study adopted two techniques: firstly, Failure Modes and Effect Analysis (FMEA) to recognise the failure modes and potential causes for blade damage, and secondly, the fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for assessing the potential causes that have been identified. It was found that the most dominant potential causes of blade damage is caused by lightning strike. Lightning tests were conducted for the coupon specimens and the blade specimens for both composite and biocomposite materials. The materials tested for coupon specimens are kenaf fibre, flax fibre and fibreglass with different configurations; without wire mesh, embedded wire mesh and outer-ply wire mesh in order to find the best configuration for wind turbine blade fabrication. The fibres were reinforced with a polyester (PE) matrix. Four types of damage detection were used to assess the severity of lightning damage on the composite and biocomposite blades, i.e. visual inspection, liquid dye-penetrant testing, ultrasonic guided wave, and laser-based ultrasonic scan. Based on the NDT tests performed on the coupon specimens, the best configurations are either made of flax fibre or fibreglass with embedded wire mesh. Three different types of blade specimens; i.e. fibreglass, flax-fibreglass, flax were fabricated and subjected to lightning strike. It was found that the flax blade suffers the least lightning damage compared to the blade containing fibreglass. This means that, natural fibre can be a good alternative to synthetic fibre in wind turbine blade fabrication. All the techniques can detect the lightning damage in the overall tested materials and blade structural systems but, the most effective technique are ultrasonic laser-based scan because the damage size and location of the damage can be observed clearly.